Adverse effects of orthodontic forces on dental pulp. Appearance and character. A systematic review - Huokuna Jukka; Loimaranta Vuokko; Laine Merja A; Svedström-Oristo Anna-Liisa (TAYLOR & FRANCIS LTD, 2025)
Objective: To comprehensively assess recent data on the effects of orthodontic forces on the dental pulp and to critically evaluate, whether any of the changes are permanent.
Materials and methods: Articles published between 2/2009 and 2/2022 were searched electronically on the PubMed, EMBASE and SCOPUS databases. The initial search retrieved 780 publications and, applying the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, 33 relevant articles were identified. Twenty articles fulfilled the requirements for high (n = 1) or moderate (n = 19) methodological quality and were included. All assessments were made independently by three researchers.
Results: Orthodontic forces appeared to cause a reduction in pulpal blood flow and a reduction in tooth sensibility, as indicated by increased response thresholds and increased amounts of negative responses to tooth sensibility tests. In addition, there were increases in the expression or activity levels of enzymes and neuropeptides associated with hypoxia and inflammation. Fibrotic tissue formation in the pulp was also reported.
Conclusions: Except for some histological and morphological alterations, the observed pulpal changes were in most cases only temporary, appearing within days of initiating the treatment and usually lasting for weeks. There were no clear signs of permanent damage.